The picture of smoking in my mind: a need for effective anti-smoking public service announcements based on the self-construals of smokers. (June 2022) - Önen, Mutlu; Watson, Forrest
This qualitative study sought to understand the behaviours of smokers with independent and interdependent self-construals to design effective anti-smoking public service announcements (PSAs). Findings from the participants' narratives and drawings suggest that individualistic message content (focused on the individual smoker) can be effective for smokers with independent self-construal, while collectivistic message content (focused on a smoker group) can be effective for smokers with interdependent self-construal to increase their quitting intentions. This study also revealed characteristics of the smoker groups in terms of routines, meanings and symbolic values of smoking, which can be used to enrich the contents for anti-smoking PSAs. The implications of this study are discussed for public policy makers and nonprofit organizations that seek to match their message with the audience to improve public health.